2017
DOI: 10.1088/1361-6420/aa777d
|View full text |Cite
|
Sign up to set email alerts
|

A novel sampling method for multiple multiscale targets from scattering amplitudes at a fixed frequency

Abstract: A sampling method by using scattering amplitude is proposed for shape and location reconstruction in inverse acoustic scattering problems. Only matrix multiplication is involved in the computation, thus the novel sampling method is very easy and simple to implement. With the help of the factorization of the far field operator, we establish an inf-criterion for characterization of underlying scatterers. This result is then used to give a lower bound of the proposed indicator functional for sampling points insid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
107
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 21 publications
4
107
0
Order By: Relevance
“…One drawback is that Theorems 2.1 and 3.2 only give that the new indicators decay as the sampling point moves away from the scatterer which may result in low contrast reconstructions. In [22] it is seen that this can be overcome by raising the new indicators to the power p > 1 to sharpen the resolution. To recover the scatterer one can take a level curve of the indicator W p .…”
Section: A Factorization Based Direct Sampling Methodsmentioning
confidence: 99%
“…One drawback is that Theorems 2.1 and 3.2 only give that the new indicators decay as the sampling point moves away from the scatterer which may result in low contrast reconstructions. In [22] it is seen that this can be overcome by raising the new indicators to the power p > 1 to sharpen the resolution. To recover the scatterer one can take a level curve of the indicator W p .…”
Section: A Factorization Based Direct Sampling Methodsmentioning
confidence: 99%
“…Inserting this into (3.1), integrating by parts and using the well-known Funk-Hecke formula [4,29], we deduce that where µ α = 2πi −α , n = 2, 4πi −α , n = 3 and f α (t) = J α (t), n = 2, j α (t), n = 3…”
Section: Direct Sampling Methodsmentioning
confidence: 98%
“…We thus expect that G (and therefore A) decays like Bessel functions as the sampling points away from the boundary of the scatterer. Then one may look for the scatterers by using the following indicators [27,29,37] with phased far field patterns, where A and G are given in (3.1). In [29], it has been showed that the indicator I 2 has a positive lower bound for sampling points inside the scatterer, and decays like Bessel functions as the sampling points away from the boundary.…”
Section: Direct Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, it is noted that Ω is unknown, but with the far-field data given in (1.3), one can apply, e.g. the direct sampling method in [21], to easily find a point inside Ω. Then associated with the far-field data given in (1.3) and for each k ∈ I, one can solve the discretized linear integral equation (2.2) by the Picard's theorem.…”
Section: 1mentioning
confidence: 99%